Presenting characteristics, comorbidities, and outcomes among 390 patients hospitalized with COVID-19 pneumonia in a tertiary hospital - Araç, Songül; Özel, Mehmet; Aslan, Aydın; Alpar, Suleyman; Araç, Eşref (The European Research Journal, 2021)
Objectives: In this study, demographic characteristics, comorbidities, presenting symptoms, physical examination findings, laboratory findings, and administered drugs of the discharged or deceased patients admitted to our hospital and hospitalized with the COVID-19 diagnosis were compared to investigate the factors that affect mortality. Methods: A retrospective study was performed and included COVID-19 pneumonia patients. 390 consecutive discharged or deceased patients, who were hospitalized in our hospital between March 20 and May 20, 2020, after detection of pneumonia and diagnosis of COVID-19, were included in the study. Results: Of the 390 patients included in the study, 352 (90.25%) were discharged after recovery, while 38 (9.75%) were deceased. The average age of all the patients was 49.46 ± 17.86 years, the average age of the discharged patients was 47.19 ± 16.76 years, and the average age of the deceased patients was 70.42 ± 13.7 years. The average age of deceased patients was significantly higher. Of all the patients, 40.8% was PCR positive. Conclusions: The present study revealed that the drugs that patients take due to their comorbidities have no effect on the prognosis of the disease and that the presence of comorbidity itself is indicative of the poor prognosis. Taking into account the PCR positivity of 57.9%, even in deceased patients, we believe PCR is inadequate in the diagnosis, and CT is much more valuable in this regard.